A REVIEW ON NETWORK PERFORMANCE EVALUATION OF 6TO4 TUNNELING - Masduki Khamdan Muchamad; Muhammad Tosan Bingamawa (Jurnal Komputer, Informasi Teknologi, dan Elektro, 2021)
In the last decade, the number of internet users is growing rapidly. With the high demand of internet users, the use of Internet Protocol (IP) addresses is nearly overused. From this problem, an alternative to overcome the IP address problem is required. IPv6 is one of the potential implementation IP addresses to replace the use of IPv4. Currently, network implementation using IPv4 – IPv6 are used simultaneously. This method is known as the transition mechanism. In this paper, a critical review analysis is performed for network performance evaluation of 6to4 tunneling. In conclusion, some of the suggestions are given as an improvement for further study.